A survey of path planning of industrial robots based on rapidly exploring random trees - Luo, Sha; Zhang, Mingyue; Zhuang, Yongbo; Ma, Cheng; Li, Qingdang (Frontiers in Neurorobotics, 2023)
Path planning is an essential part of robot intelligence. In this paper, the characteristics of path planning of industrial robots are summarized. Owing to the probabilistic completeness, the rapidly-exploring random tree (RRT) algorithm is widely used in the path planning of industrial robots. Aiming at the shortcomings of the RRT algorithm, this paper investigates the RRT algorithm for path planning of industrial robots in order to improve its intelligence. Finally, the future development direction of the RRT algorithm for path planning of industrial robots is proposed. The study results have particularly guided significance for the development of the path planning of industrial robots and the applicability and practicability of the RRT algorithm.